Analysis of Space Designation Direction Based on Building Area Coefficient, Accessibility, and Building Function: Study on Lakidende University Development Plan - Haydir Haydir; Adris Ade Putra; Armita Amelia; Asrul Asrul; Hasddin Hasddin; La Karimuna; Jasman Jasman; Rudi Azis; Alkadri Alkadri; Taufik Taufik; Asri Nova Roma; Yola Lestari (Logistic and Operation Management Research (LOMR), 2025)
The growing population and increasing demand for space have made spatial planning a critical component of sustainable development. In a campus environment, efficient spatial organization supports both academic and social functions. With Lakidende University experiencing a rise in student numbers, strategic space utilization has become essential. This study analyzes the spatial development direction of Lakidende University based on building coefficient, accessibility, and building functions. A qualitative approach with a quantitative descriptive design was applied. Data were collected through field observations, documentation, and document review. Key variables included the building coverage ratio (minimum 30%), accessibility, and functional use of buildings. The analysis compared existing campus conditions with relevant spatial regulations. Tools such as ArcGIS and SketchUp supported site planning analysis. The findings indicate that Lakidende University, spanning 30,000 m², has 27,197.16 m² of non-buildable land (8.1%), while the current building coefficient reaches the minimum threshold of 30%. The available development area is 8,159.15 m². Based on the number of students, lecturers, and staff in 2023, projected spatial needs for new faculty buildings, a library, canteens, parking, and open areas amount to 5,964.5 m². This remains within the allowable development area. The results demonstrate adequate space for future expansion. This research offers fresh insight into campus spatial planning at Lakidende University, addressing previously unexamined gaps. By evaluating land use coefficients, accessibility, and spatial functions, the study presents practical strategies for efficient space management to support long-term institutional growth and sustainability.